The Role of Bank Capital in Bank Holding Companies' Decisions - Barajas, Adolfo; Cosimano, Thomas; Hakura, Dalia; Roelands, Sebastian (Washington, D.C. : International Monetary Fund, 2015)
This paper examines the role of bank capital in decision-making by bank holding companies (BHCs) in the United States. Following Chami and Cosimano's (2001) call option approach to bank capital, BHCs optimally choose the amount of capital to insure the bank against becoming capital constrained in the future. We provide empirical support for this model, and find that a higher optimal level of capital leads to higher loan rates. Furthermore, higher loan rates result in lower amounts of lending. Thus, an increase in capital requirements is likely to lead to higher loan rates and a significant reduction in lending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet